Italy in a European Context Research in Business, Economics, and the Environment - Strangio, Donatella; Sancetta, Giuseppe; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This edited collection investigates the role of Italy in pursuing the EU five targets by 2020: R&D/innovation expenditures; the energetic measures for climate change; migration; the counter actions against poverty and social exclusion. This ambitious book uses a multidisciplinary approach and original field studies to tackle this important topic.
Keywords: Environmental economics; Economic policy; Macroeconomics; International economics; Political economy; Economics; Environmental Economics; Economic Policy; Macroeconomics/Monetary Economics//Financial Economics; International Economics; International Political Economy; Political Economy/Economic Systems